PERLINDUNGAN KONSUMEN DALAM PERKARA HUKUM KEPAILITAN - Tandean Laurencia (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2021)
Abstract: “Bankruptcy and suspension of debt obligations is one of the dispute resolution mechanisms that parties can choose to resolve problems in an efficient and transparent manner. This mechanism is governed by Law No. 37 of 200 On Bankruptcy and Suspension of Debt Service (Bankruptcy Law). However, the law encountered many obstacles in the implementation process, mainly related to the protection of consumer rights. This article will cover the bankruptcy of the consumer position and its implementation. The author notes that the position of consumers in bankruptcy is governed not only by insolvency law but also by the Civil Code, Law No. 8 of 1999 on the protection of consumer rights. The guidelines on these regulations raise a number of problems, namely the lack of clarity and regulation as well as the violation of the principles of law. As a result, the consumer has a very weak position. Therefore, the law of default should clearly define the position of consumers; while regulations related to its supervision must also be strengthened; and severe penalties should also be imposed for any wrongdoing by law enforcement. At the same time, other laws must align their provisions with insolvency laws for effective implementation. Keywords: Legal Protection, Consumer, Bankruptcy